Respuesta :

Here you go.

I was sorta unsure how to read the last part in your question but I tried my best to interpret it 
Ver imagen tinmann

For this case we have the following quadratic equation:

[tex] x ^ 2 = 19x + 1 [/tex]

Rewriting we have:

[tex] x ^ 2 - 19x - 1 = 0 [/tex]

Then, using the quadratic formula we have:

[tex] x =\frac{-b+/-\sqrt{b^2-4ac}}{2a} [/tex]

Substituting values:

[tex] x =\frac{-(-19)+/-\sqrt{(-19)^2-4(1)(-1)}}{2(1)} [/tex]

Rewriting:

[tex] x =\frac{19+/-\sqrt{361+4}}{2} [/tex]

[tex] x =\frac{19+/-\sqrt{365}}{2} [/tex]

Therefore, the solutions are given by:

[tex] x =\frac{19+\sqrt{365}}{2} [/tex]

[tex] x =\frac{19-\sqrt{365}}{2} [/tex]

Answer:

The solutions of the equation are:

[tex] x =\frac{19+\sqrt{365}}{2} [/tex]

[tex] x =\frac{19-\sqrt{365}}{2} [/tex]